Assessment of the Changes in Hormones of Somatotropic Axis during Transition Period in Murrah Buffaloes (Bubalus bubalis) Supplemented with Vitamin E - Mili, Bhabesh; Pandita, Sujata; Kumar, B. S. Bharath; Parmar, Mehtab S. (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
The goal of this study was to see how vitamin E supplementation affected the GH-insulin–IGF-1 axis in Murrah buffaloes throughout the transition phase. The Murrah buffaloes (n = 12) were chosen from the National Dairy Research Institute (NDRI) cattle herd during their late gestation and divided into two groups of six each. Group I buffaloes were fed simply the control diet, whereas group II buffaloes were given 2000 IU/day/head vitamin E combined with the control feed. Blood sample were collected from each buffalo at weekly interval from day -21 to day +21 relative to parturition by jugular veinpuncture. Growth hormone (GH) -IGF-1 and insulin were quantified by bovine specific ELISA test kit. During the transition phase, there was no significant difference in insulin and GH concentrations in the blood between the two groups, according to the findings. However, the amount of insulin and IGF-I reduction was much larger in Group I. The fall in these hormone levels during the transition phase was determined to be a physiological event linked to a negative energy balance. During the transition phase, dietary treatment with Vitamin E showed no effect on peripheral profiles of these hormones.